Using Digital Marketing for Small and Medium Enterprises (SMEs) in Bumdes Remboko Sumberrejo Village Sleman Regency - Zain Maulana; Muhammad Chanif Hidayat; Imaniar Agustina (Universitas Ahmad Dahlan, 2022)
Background: This community service aims to assist and empower the small and medium enterprises (SMEs) of the UMKM Bumdes Remboko to have highly digital marketing in Yogyakarta. Also, it focuses on maximizing the use of the internet specifically social media and the marketplace for branding, promoting, and selling its products. This study emphasizes that SMEs need to embrace digital technology in performing their business. Contribution: Empowerment is important because it upgrades the small and medium enterprises to face competition with others. Method: Several activities including creating a social media account, photography training, webinar, and registering of Go-Food were used to increase the SMEs' abilities in using the internet. Results: The results showed that these activities help SME partners of Bumdes Remboko use digital marketing through social media and the marketplace. Conclusion: In conclusion, it is expected that small and medium enterprises increase their business by using digital methods